2011
DOI: 10.1007/s00464-011-1633-1
|View full text |Cite
|
Sign up to set email alerts
|

The use of curved vs. straight instruments in single port access surgery, on standardized box trainer tasks

Abstract: BackgroundSingle-port access (SPA) surgery is a novel surgical technique to create nearly “scarless” surgery. SPA surgery appears to be safe and feasible, but the exposure and handling of tissue may not be optimal. Therefore, the performance of SPA surgery with different instruments used and conventional laparoscopy is compared.MethodsFifteen participants (>50 laparoscopic procedures) performed three basic tasks (translocation, clip & cut, and tissue dissection, based on the fundamentals of laparoscopic surger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 18 publications
0
15
0
1
Order By: Relevance
“…In the task of peg transferring, participants using two conventional straight instruments perform better than the other three groups in the beginning because of the simplicity of the task and their familiarity with the conventional straight instruments. With the increasing complexity of pattern cutting, the specially designed instruments demonstrate the superiority, gaining a higher score . Participants require more drills to reach the pattern‐cutting plateau with all four sets of instruments, which may indicate LESS itself contributes more to the increased length of the learning curve than the specific instruments.…”
Section: Discussionmentioning
confidence: 98%
“…In the task of peg transferring, participants using two conventional straight instruments perform better than the other three groups in the beginning because of the simplicity of the task and their familiarity with the conventional straight instruments. With the increasing complexity of pattern cutting, the specially designed instruments demonstrate the superiority, gaining a higher score . Participants require more drills to reach the pattern‐cutting plateau with all four sets of instruments, which may indicate LESS itself contributes more to the increased length of the learning curve than the specific instruments.…”
Section: Discussionmentioning
confidence: 98%
“…The most important is loss of triangulation between the two instruments due to their parallel entry through the single port which makes dissection more difficult with deceased visualization and exposure [20,21]. Sword-fighting of the laparoscope and instruments around the umbilicus is another added problem.…”
Section: Discussionmentioning
confidence: 99%
“…We therefore replaced these instruments with a conventional rigid instrument in the dominant hand and a curved one in the other hand, whereby the curved instrument was used to fix the tissue and the rigid instrument was used for the major handling during surgery, and found that this set-up decreased handling difficulties. Botden et al 16 reported that conventional rigid instruments can also be used to successfully perform the LESS procedure, but we consider that a curved instrument can increase the angle of the instruments and thus provide a better handling view. Moreover, the curved instruments we used were 5 cm longer than the rigid instruments, which meant that the two hands were not at the same level, and this therefore reduced interference between the hands (Fig.…”
Section: Technical Experiences Of Less Adrenalectomymentioning
confidence: 98%